Comparative transcriptome analysis reveals candidate genes for the biosynthesis of natural insecticide in Tanacetum cinerariifolium. (December 2017) - Khan, Sana; Upadhyay, Swati; Khan, Feroz; Tandon, Sudeep; Shukla, Rakesh; Ghosh, Sumit; Gupta, Vikrant; Banerjee, Suchitra; ur Rahman, Laiq
Abstract Background Pyrethrins are monoterpenoids and consist of either a chrysanthemic acid or pyrethric acid with a rethrolone moiety. Natural pyrethrins are safe and eco-friendly while possessing strong insecticidal properties. Despite such advantages of commercial value coming with the eco-friendly tag, most enzymes/genes involved in the pyrethrin biosynthesis pathway remain unidentified and uncharacterized. Since the flowers ofTanacetum cinerariifolium are rich in major pyrethrins, next generation transcriptome sequencing was undertaken to compare the flowers and the leaves of the plantde novo to identify differentially expressed transcripts and ascertain which among them might be involved in and responsible for the differential accumulation of pyrethrins inT. cinerariifolium flowers. Results In this first tissue specific transcriptome analysis of the non-model plantT. cinerariifolium, a total of 23, 200, 000 and 28, 500, 110 high quality Illumina next generation sequence reads, with a length of 101 bp, were generated for the flower and leaf tissue respectively. After functional enrichment analysis and GO based annotation using public protein databases such as UniRef, PFAM, SMART, KEGG and NR, 4443 and 8901 unigenes were identified in the flower and leaf tissue respectively. These could be assigned to 13344 KEGG pathways and the pyrethrin biosynthesis contextualized. The 2-C-methyl-D-erythritol 4-phosphate (MEP) pathway was involved in the biosynthesis of acid moiety of pyrethrin and this pathway predominated in the flowers as compared to the leaves. However, enzymes related to oxylipin biosynthesis were found predominantly in the leaf tissue, which suggested that major steps of pyrethrin biosynthesis occurred in the flowers. Conclusions Transcriptome comparison between the flower and leaf tissue ofT. cinerariifolium provided an elaborate list of tissue specific transcripts that was useful in elucidating the differences in the expression of the biosynthetic pathways leading to differential presence of pyrethrin in the flowers. The information generated on genes, pathways and markers related to pyrethrin biosynthesis in this study will be helpful in enhancing the production of these useful compounds for value added breeding programs. Related proteome comparison to overlay our transcriptome comparison can generate more relevant information to better understand flower specific accumulation of secondary metabolites in general and pyrethrin accumulation in particular.